Students' learning strategies and cognitive engagement : a case study at International Islamic School Gombak (ISS) - Sani, Abubakar (Institute of Education, International Islamic University Malaysia, 2014)
This study investigates the relationship between learning strategies and cognitive engagement among secondary school students at the International Islamic School (IIS), Gombak, Malaysia. Specifically the objectives of this study are to determine the most often used learning strategy among the students in their English language classrooms and to measure the students' level of cognitive engagement based on gender, age and grades. Three learning strategies are adopted in the study which are cognitive, metacognitive and social. The study covers 130 participants aged ranging between 13 and 18 years. Data were collected using a questionnaire, employing a 5 point Likert's scale. Descriptive statistics and correlations as statistical inferences were employed in describing and testing the relationships between learning strategies and cognitive engagement. The findings reveal that students employ all the three learning strategies with similar pattern levels of cognitive engagement based on gender, age and grades. It was found that students aged 13 and 15 display higher deep engagement as well as low shallow engagement. In addition, significant and positive correlations were found between cognitive, meta-cognitive and social strategies with cognitive engagement. Subsequently, a significant negative correlation was also found between deep and shallow engagement, portraying an inverse relationship.